“Cleaved Tau Protein”: A Novel Biomarker Candidate in Mild Neurotrauma in Emergency Settings - Pandey, Sharad; Singh, Kulwant; Pandey, Deepa; Chand, Gian; Sharma, Vivek; Jha, Ravi Prakash; Singh, Royana; Rai, Sunil Kumar; Gupta, Rashmi (Indian Journal of Neurotrauma, 2017)
Background Neurotrauma has been labeled as a “silent epidemic” affecting both the developed and the developing nations. Traumatic brain injury (TBI) in humans leads to the proteolytic cleavage of tau protein called cleaved tau (C-tau) protein. The objectives of the study are to the role of serum cleaved tau (C-tau/τC) protein as a biomarker in patients with mild TBI and correlate it with the clinical progression (GCS) and clinical outcome (GOS) in emergency settings.Materials and Methods The study has been approved by the institutional ethical committee. The study included 40 cases with mild TBI and 40 controls. C-tau protein levels were measured in venous samples in emergency using human cleaved microtubule-associated protein tau ELISA kit (by CUSABIO).Results The mean serum C-tau protein level in cases was 44.76 ± 23.10 pg/mL (range: 12.32–96.44, 95% CI: 37.37–52.15) and controls was 33.82 ± 13.65 pg/mL, (range: 2.48–66.54, 95% CI: 29.46–38.19, p = 0.091). At admission the mean serum C-tau level was 65.15 ± 22.41, 43.87 ± 9.67, 26.15 ± 9.13 pg/mL in patients with GCS 13, 14, and 15, respectively. Serum cleaved tau protein levels in the good outcome group were significantly lower, that is, 40.77 ± 19.63 pg/mL (mean ± SD) (range: 12.32–88.71, 95% CI: 34.13–47.42) compared with the poor-outcome group 80.66 ± 23.10 pg/mL (mean ± SD) (range: 46.55–96.44, 95% CI: 43.88–117.43, p = 0.004).Conclusion In this study, serum C-tau levels in patients with mild TBI were comparatively higher than those in the controls. Reaching a definitive conclusion will be too early and beyond the scope of this study. Thus, more studies are required in identifying its role as a diagnostic and prognostic marker in mild TBI.
Keywords: serum cleaved tau protein; mild traumatic brain injury; emergency; diagnostic; prognostic marker